Impact of digital transformation on HR in a corporate world - Maheen, Saarina; Kašparová, Eva, 1958-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The main objective of this thesis is to analyze the importance of digital transformation in the corporate world and understand how it is affecting HRM in creating a sustainable business. Furthermore, the study involves identification of problems created by the digital transformation in the workplace and comes up with potential solutions to these problems. This theoretical analysis is also put into practical approach by carrying out case studies on two global companies that are namely: Huawei Investment and Holding Co., Ltd and EY Co. Ltd; one of which is known for technological operations and the other for business service providers. Finally, a conclusion is drawn by comparing the impact of digital transformation on the two companies with completely different operational sectors.
Vedoucí práce: Eva Kašparová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses